Impact of AI on Future Roles for B-School Graduates - Kedari, Sirisha (The Hans India, 2025)
Siddharth Shahani, Co-Founder and Executive President of ATLAS SkillTech University, shares his insights in The Hans India on how AI is reshaping management careers, underscoring the growing need for interdisciplinary thinking, AI-powered decision-making and leaders who can translate data into strategic impact.
Please click on the link to refer the whole article.